Proposed Total Productive Maintenance (TPM) Implementation to Increase Heading Machine Effectiveness Using Overall Equipment Effectiveness (OEE) Method on PT. XYZ - Leke, Rupertus Mario Serapion; Saifuddin, Joumil Aidil (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
PT XYZ is one of the companies engaged in the precast concrete manufacturing industry which is specially designed to meet the needs of industrial markets such as high-quality building and building construction. The machine under study is the machine used for assembling the spun pile reinforcement frame in the rotary workshop. The purpose of this study is to analyze the application of Total Productive Maintenance (TPM) through the effectiveness and efficiency of heading machine performance and analyze the factors that affect the Overall Equipment Effectiveness (OEE) value and present a proposed heading machine maintenance strategy. The method used is OEE with Six Big Losses analysis. For the analysis of the six big losses on the OEE value, namely the value of Idle and minor stoppage (a decrease due to many machine stops) which is a factor that has the largest percentage of the six big losses with a resulting factor value of 7.0%. Then followed by reduced speed losses (decrease in engine speed) of 3.96% and then deffect losses of 3.48% and the three other factor values, namely breakdown losses, setup losses, and yield losses. Measurement of the level of effectiveness and efficiency of the heading machine at PT XYZ using the OEE method for the period 2022 in January - December obtained an average value of 78.28%. The resulting value is still far from the ideal OEE standard value of 85% which refers to the world class standard. The lowest OEE factor value is obtained from the calculation of Performance Efficiency of 86.29% where it is necessary to update the machine maintenance scheduling so as to increase the efficiency of the heading machine performance that supports the production speed of the company.